Densidade mineral óssea, exercício físico no lazer e composição corporal em mulheres pós-menopausa: estudo com usuárias do Sistema Único de Saúde - Locci, Bruna [UNESP] (2015)
The aim of the study was to analyze the relationship between bone mineral density, physical exercise in leisure and components of body composition in postmenopausal users of the health care system. Thus, we selected randomly 176 menopausal women, aged ≥ 50 years who were part of a survey of 963 users of five basic health units (BHU) in the city of Bauru, the state of São Paulo. The physical exercise in leisure, ethnicity, smoking, socioeconomic status and educational level were obtained through a survey completed by interviews. Body composition measurements and bone mineral density (BMD) were obtained by taking absorptiometry dual energy x-ray absorptiometry (DXA), and anthropometric parameters were collected before the densitometry exam. First, to analyze the relationship of physical activity at leisure on the distribution of fat mass was observed relationship between higher intensity (rho = -0.17; p-value = 0.022) and higher prior period of engagement (rho = -0.15 ; p-value = 0.041) in leisure activities with lower fat values in the trunk, however, this relationship ceased to present statistical significance when corrected for some confounders. In the next stage, which were included only 144 women, to evaluate the relationship between bone mineral density, physical exercise in leisure and components of body composition was observed that the BMD was positively correlated with lean body mass, but not with fat and practice exercises at leisure. In summary, it was observed that for this population, in practice intended for leisure time occur intensity, duration and time prior to engagement insufficient to cause significant changes in body composition and also no relation with BMD. However, total lean mass was shown to be a protective factor for osteoporosis, indicating that the development of resistance exercise in order to increase or maintain lean body mass may have preventive and therapeutic effect significant for the prevention/ ...